MR Imaging Features of the Cerebellum in Adult-Onset Neuronal Intranuclear Inclusion Disease: 8 Cases - Sugiyama, A.; Sato, N.; Kimura, Y.; Maekawa, T.; Enokizono, M.; Saito, Y.; Takahashi, Y.; Matsuda, H.; Kuwabara, S. (American Journal of Neuroradiology, 2017)
SUMMARY: Neuronal intranuclear inclusion disease is a neurodegenerative disorder pathologically characterized by eosinophilic hyaline intranuclear inclusions. A high-intensity signal along the corticomedullary junction on DWI has been described as a specific MR imaging finding of the cerebrum in neuronal intranuclear inclusion disease. However, MR imaging findings of the cerebellum in neuronal intranuclear inclusion disease have not been fully evaluated. Here, we review MR imaging findings of the cerebellum in a series of 8 patients with pathologically confirmed neuronal intranuclear inclusion disease. The MR imaging results showed cerebellar atrophy (8/8 patients) and high-intensity signal on FLAIR images in the medial part of the cerebellar hemisphere right beside the vermis (the “paravermal area”) (6/8) and in the middle cerebellar peduncle (4/8). The paravermal abnormal signals had a characteristic distribution, and they could be an indicator of the diagnosis of neuronal intranuclear inclusion disease even when using the results of past MR imaging examinations in which DWI findings were not examined.FABFrontal Assessment BatteryFXTASfragile X-associated tremor/ataxia syndromeMMSEMini-Mental State ExaminationNIIDneuronal intranuclear inclusion disease